Exploring herbaceous plant biodiversity design in Chinese rain gardens: a literature review - Shi, Lin; Maruthaveeran, Sreetheran; Yusof, Mohd Johari Mohd; Zhao, Jing; Liu, Ruosha (Multidisciplinary Digital Publishing Institute, 2024)
Amidst rapid urbanization and escalating environmental degradation in China’s urban areas due to climate change, traditional drainage systems struggle to cope with rainfall, resulting in frequent flood disasters. In response, rain gardens have emerged as ecologically practical stormwater management solutions that integrate urban flood control with landscape design. Leveraging the dual benefits of rainwater purification and aesthetic enhancement provided by vegetation, herbaceous plant-based rain gardens have assumed a pivotal role in green infrastructure. However, dedicated research on the application of herbaceous plants in rain garden design is limited, especially within China’s water-stressed context. This study employs a literature review and case analysis to explore this critical issue. Initially, it delineates the concept of the sponge city introduced by the Chinese government. Subsequently, it reviews concepts and methods of plant biodiversity design in urban settings and rain gardens and elucidates the structure and function of rain gardens. Four Chinese rain gardens in different urban environments (old industrial areas, university campuses, urban villages, and urban highway green belts) were selected to examine the selection and arrangement of herbaceous plants while identifying deficiencies in their designs. Finally, feasibility suggestions are provided for the design of herbaceous plant diversity in Chinese rain gardens. This study’s findings can provide a reference for the planting design of herbaceous plants in rain gardens for other countries and regions with similar climates and environmental conditions.